Konstytucyjność algorytmicznego wymierzania kary w prawie karnym w Polsce - Kisiel, Jakub (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
This article addresses the issue of the constitutionality of the use of algorithms in sentencing. The author focuses on the analysis of two key provisions of the Constitution regulating the presumption of innocence and the right to a court. The study shows that an algorithm cannot be a court in the meaning of the Constitution. However, it is possible to use algorithms on a similar basis as regarding the procedure on ticketing for traffic offences.